Antiplatelet therapy and outcome in patients with COVID-19. Results from a multi-center international prospective registry (HOPE-COVID19). (14th October 2021) - Santoro, F; Vitale, E; Nunez Gil, I; Guerra, F; El-Battrawy, I; Brunetti, N D
Abstract: Background: No standard therapy is currently recommended for Corona-virus-19 disease (COVID-19). Autopsy studies showed high prevalence of platelet-fibrin rich micro-thrombi in several organs. Aim of the study was to evaluate safety and efficacy of antiplatelet therapy (APT) in COVID-19 hospitalized patients and its impact on survival. Methods: 7824 consecutive patients with COVID-19 were enrolled in a multicenter-international prospective registry (HOPE-COVID19). Clinical data and in-hospital complications were recorded. AP regimen, including aspirin and other antiplatelet drugs, was obtained for each patient. Results: During hospitalization 730 (9.3%) patients received AP drugs with single (93%, n=680) or dual APT (7%, n=50). Patients treated with APT were older (73±12 vs 62±17 years, p<0.01), more frequently male (70% vs 64%, p<0.01) and had higher prevalence of diabetes (39.5% vs 17%, p<0.01). Patients treated with APT showed no differences in terms of in-hospital mortality (18% vs 19%, p=0.64, Log Rank p=0.23), need of invasive ventilation (8.7% vs 8.5%, p=0.88) and bleeding (2.1% vs 2.4%, p=0.43); However, after excluding patients treated only with anticoagulation, APT was associated with lower mortality rates (Log Rank p<0.01, relative risk 0.79, 95% CI 0.70–0.94) (Figure 1). At multivariable analysis including age, gender, diabetes, hypertension, respiratory failure, pre-hospital therapy with antiplatelet drugs, in-hospital APT, and anticoagulation therapy, in-hospital APT was associated with a lower mortality risk (relative risk 0.29, 95% CI 0.22–0.38, p<0.001). Conclusions: APT during hospitalization for COVID-19 could be associated with lower mortality risk without increased risk of bleeding. Randomized trials are needed to confirm these preliminary data. FUNDunding Acknowledgement: Type of funding sources: None.